Analysis Of Implementation Of Innovation In Cooperation Between Government, Banks And Business In Developing Msmes In Central Maluku Regency - Mauwa Latupono; Maryam Sangadji; Jopie Tamtelahitu (LP2M IAIN Palopo, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the regional economy, yet they still face limitations in access to financing and business capacity. The Central Maluku Regency Government has developed policy innovations through Government, Bank, and Business Cooperation in the development of MSMEs. This study aims to analyze the implementation of these collaborative innovations and their impact on MSME development in Central Maluku Regency. The study employed a mixed methods approach, with qualitative analysis to examine the policy implementation process and quantitative analysis through regression to examine the program's impact on MSME performance. Data were obtained through interviews, questionnaires, observations, and documentation studies. The results indicate that the implementation of collaborative innovations has progressed through the stages of socialization, data collection, financing distribution, mentoring, and monitoring and evaluation. The regression analysis indicates that the implementation of collaborative innovations between the government, banks, and businesses has a positive and significant impact on MSME development.